2020
DOI: 10.1080/22221751.2020.1827985
|View full text |Cite
|
Sign up to set email alerts
|

Robust and persistent SARS-CoV-2 infection in the human intestinal brush border expressing cells

Abstract: Studies on patients with the coronavirus disease-2019 (COVID-19) have implicated that the gastrointestinal (GI) tract is a major site of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We established a human GI tract cell line model highly permissive to SARS-CoV-2. These cells, C2BBe1 intestinal cells with a brush border having high levels of transmembrane serine protease 2 (TMPRSS2), showed robust viral propagation, and could be persistently infected with SARS-CoV-2, supporting the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 52 publications
4
60
0
Order By: Relevance
“…Efforts to model GI infection in vitro led to identification of four colon carcinoma cell lines (human intestinal epithelial cells [IECs]) that are permissive to SARS-CoV-2 infection: Caco-2 ( 49 , 128 ) (also susceptible to the SARS-CoV infection) ( 129 ); C2BBe1, the Caco-2 brush border-expressing subclone ( 130 ); CL14 ( 131 ); and T84 ( 128 ). However, most niche-mimicking models and models of the GI tract are based on the use of human intestinal organoids (HIOs), which are currently the most advanced tool available.…”
Section: The Gastrointestinal Tractmentioning
confidence: 99%
“…Efforts to model GI infection in vitro led to identification of four colon carcinoma cell lines (human intestinal epithelial cells [IECs]) that are permissive to SARS-CoV-2 infection: Caco-2 ( 49 , 128 ) (also susceptible to the SARS-CoV infection) ( 129 ); C2BBe1, the Caco-2 brush border-expressing subclone ( 130 ); CL14 ( 131 ); and T84 ( 128 ). However, most niche-mimicking models and models of the GI tract are based on the use of human intestinal organoids (HIOs), which are currently the most advanced tool available.…”
Section: The Gastrointestinal Tractmentioning
confidence: 99%
“…In another study, Lee et al, have utilized the human intestinal cell line (C2BBe1), characterized by high levels of TMPRSS2 and ACE2, to study the role of ACE2 and TMPRSS2 in SARS-CoV-2 infection of GI tract. The authors found that the cells demonstrated persistent infection with SARS-CoV-2 and robust viral propagation [ 26 ]. It’s noteworthy to mention that the C2BBe1 cells are brush border expressing cells with microvilli resembling the brush border of human intestinal epithelia [ 26 ].…”
Section: Tmprss2 and Sars-cov-2 Infection Of Gastrointestinal Tract Systemmentioning
confidence: 99%
“…The authors found that the cells demonstrated persistent infection with SARS-CoV-2 and robust viral propagation [ 26 ]. It’s noteworthy to mention that the C2BBe1 cells are brush border expressing cells with microvilli resembling the brush border of human intestinal epithelia [ 26 ].…”
Section: Tmprss2 and Sars-cov-2 Infection Of Gastrointestinal Tract Systemmentioning
confidence: 99%
“…Recently, we and others have shown that SARS-CoV-2 infects the human cells through host factors ACE2 and TMPRSS2 and replicates in various human epithelial cells 7,8 . In order to investigate SARS-CoV-2-induced alteration in intracellular events which affect a rapid and sustained viral propagation, we first analysed the aspects of SARS-CoV-2 infectivity and replication in several human cells including human normal primary bronchial cells as evidenced by confocal microscopy using anti-SARS-CoV-2 nucleocapsid antibody, real-time qRT-PCR using primer sets specific to SARS-CoV-2 nucleocapsid gene, and Western blot analysis with antibodies specific to SARS-CoV-2 spike and nucleocapsid antigens (Extended Data Fig.…”
Section: Sars-cov-2 Aberrantly Elevates Mitochondrial Bioenergeticsmentioning
confidence: 99%
“…SARS-CoV-2 phylogenetically closely related to SARS-CoV causing an epidemic in 2003 3,4 is an enveloped, single-stranded positive-sense RNA virus belonging to the family Coronaviridae 5 . SARS-CoV-2 enters into the host cells via host factors angiotensin-converting enzyme carboxypetidase (ACE2) and transmembrane serine protease 2 (TMPRSS2) and utilizes own RNA-dependent RNA polymerase (RdRp) for the replication of viral genome in the cytoplasm [6][7][8] . In particular, when SARS-CoV-2 infects cells by ACE2-mediated endocytosis, SARS-CoV-2 nucleocapsid protein binding to the packaging signals in the virus RNA (SARS-CoV-2 RNA-nucleocapsid cluster) enters into the cells 9,10 unlike other RNA viruses such as hepatitis C virus (HCV) and Zika virus (ZIKV) and so on 29,30 .…”
Section: Introduction 39mentioning
confidence: 99%